Places of curriculum making narrative inquiries into children's lives in motion - Huber, Janice; Murphy, M. Shaun; Clandinin, D. Jean.; Kukner, Jennifer Lisa Mitton; Orr, Anne Murray (Bingley, U.K. : Emerald, 2011)
This book documents a radical shift in thinking from focusing on the school as the place where curriculum is made to realizing the ways children and families are engaged as curriculum makers in homes, in communities, and in the spaces in-between, outside of school. The narrative inquiry framing this book investigates the tensions experienced by teachers, children and families as they make curriculum attentive to lives. It draws on a research project involving multi-perspectival narrative inquiries spanning four research sites and traces the tensions experienced by children, families and teachers in multiple curriculum making sites and some of the profound identity making and assessment making implications that become visible. Its attention to the relational in narrative inquiry is focused on tensions that shape lives and, as well, the unfolding of narrative inquiries. This informative book has a wide reaching audience of educational researchers, teacher educators, research methodologists, particularly those interested in narrative inquiry, curriculum scholars, graduate students, university faculty, teachers, administrators and parents alike.
ch. 1. Interrupting understandings of curriculum making / Janice Huber, M. Shaun Murphy, D. Jean Clandinin -- ch. 2. Narrative inquiry as relational multiperspectival inquiry / Janice Huber, M. Shaun Murphy, D. Jean Clandinin -- ch. 3. Loyla's familial curriculum making in the home and community / Janice Huber, M. Shaun Murphy, D. Jean Clandinin -- ch. 4. Ji-Sook's and Brent's stories to live by / Janice Huber, M. Shaun Murphy, D. Jean Clandinin -- ch. 5. The school curriculum making of Ji-Sook and Brent / Janice Huber, M. Shaun Murphy, D. Jean Clandinin -- ch. 6 The familial curriculum making of Ji-Sook, Brent, and their families / Janice Huber, M. Shaun Murphy, D. Jean Clandinin -- ch. 7. Living in two worlds of curriculum making / Janice Huber, M. Shaun Murphy, D. Jean Clandinin -- ch. 8. Conceptualizing curriculum making as interwoven with identity making and assessment making / Janice Huber, M. Shaun Murphy, D. Jean Clandinin -- ch. 9. Worlds and, of necessity, world travel / Janice Huber, M. Shaun Murphy, D. Jean Clandinin.
Includes bibliographical references (p. 153-156).
Keywords: Curriculum planning